2001
DOI: 10.1002/app.1491
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal aging and tensile behavior of injection‐molded rice husk‐filled polypropylene composites

Abstract: ABSTRACT:The effect of the filler volume fraction on the tensile behavior of injectionmolded rice husk-filled polypropylene (RH-PP) composites was studied. Hygrothermal aging behavior was also investigated by immersing the specimens in distilled water at 30 and 90°C. The kinetics of moisture absorption was studied from the amount of water uptake by specimens at regular interval times. It was found that the diffusion coefficient and the maximum moisture content are dependent on the filler volume fraction and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 17 publications
5
43
0
1
Order By: Relevance
“…This could be associated with the agglomeration of bers in the matrix. 23 The exural strength of the uncompatibilized composites is still superior in comparison to PBS/PBAT blend matrix. This phenomenon once again proves that the miscanthus bers have good reinforcing capabilities in the polymer matrix.…”
Section: 22mentioning
confidence: 90%
See 1 more Smart Citation
“…This could be associated with the agglomeration of bers in the matrix. 23 The exural strength of the uncompatibilized composites is still superior in comparison to PBS/PBAT blend matrix. This phenomenon once again proves that the miscanthus bers have good reinforcing capabilities in the polymer matrix.…”
Section: 22mentioning
confidence: 90%
“…Similar occurrence has been reported in exural modulus with increasing ller content in polymer matrices. 23,24 Moreover, the addition of miscanthus bers into polymer matrix resulted in superior exural properties than its matrix. 25 As mentioned before, the polymer chain mobility has been hindered in the presence of bers, consequently the composites become stiffer and have a higher exural strength as compared to their matrix.…”
Section: 22mentioning
confidence: 99%
“…Many publications have investigated the mechanical and thermal characterization of FRP under different hygrothermal conditions. The effects of moisture and applied temperature on mechanical properties of FRP are investigated in the literature [5][6][7][8][9][10][11][12][13][14]. In detail, Bajracharya et al [5] reviewed the mechanical properties and durability of glass fiber reinforced recycled mixed plastic waste composites.…”
Section: Introductionmentioning
confidence: 99%
“…They found that moisture absorption was a critical factor that controlled the thermal and mechanical properties of GFRP rebar. Mohd Ishak et al [9][10][11] have done many works on the hygrothermal aging properties of fiber reinforced polymer composites. Tajvidi et al [12] and Ellyin et al [13] have investigated the effect of temperature on different composites.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these perfect covalent bondings, there are still some un-reacted silanol groups, polar groups of lubricants or surfactants [15] and other weak points in the interphase, which are liable to interact with [16] and accommodate water molecules, leading to the degradation of interphase properties, correspondingly, the mechanical properties of composites. When the non-hygroscopic features of GFs and PP are taken into consideration [17], it becomes obvious that proper interphase design holds great promise to improve the hygrothermal durability of composites [3]. However, as yet reports addressing the further improvement of the hygrothermal durability of GF (the most widely used fibre reinforcement globally) reinforced PP composites are rather limited.…”
Section: Introduction -2 -mentioning
confidence: 99%